CHARACTERISTICS AND OUTCOMES OF AERODIGESTIVE FOREIGN BODIES IN CHILDREN - Habib, Murad; Arif, Khurrum; Chaudhary, Muhammad Amjad (Journal of Ayub Medical College Abbottabad, 2024)
Background: Aerodigestive foreign bodies are common in children of pre-school-going age. It is one of the leading cause of morbidity and mortality in the paediatric population and a global health burden. Methods: We present here data of 108 patients who presented to Children hospital’s Emergency with a suspicion of foreign body ingestion/aspiration over 2 years from July 1st 2021 to 30th June 2023. Their descriptive analysis including, socio-demographics, type of foreign body, age of presentation, and mode of presentation were calculated and correlation was done using the Pearson Chi square test. Results: We observed different types & characteristics of foreign bodies, patients were predominantly male with 62.26%. The mean age of presentation was 40.97 months. The majority of patients were of pre-school age, younger than 4 years (44.44%) followed by the infant population (19.44%) p=0.002. Foreign bodies were mainly located in the upper oesophagus for ingested FBs (60.8%). Most of the population presented within the first 5 hours (52.88%) followed by the first 12 hours (11.11%). Coin ingestion was by far the most common (54%) followed by button battery (19%) and the whistle was the most common aspirated object (33%). Conclusion: All patients with a suspicion of foreign body ingestion/inhalation should be evaluated. Early recognition and treatment are imperative because the complications are serious and can be life-threatening and once confirmed should undergo endoscopic removal.